Measurement of Diameters of Maxillary Sinuses by Computed Tomography among Patients Attending a Teaching Hospital at Pokhara - Singh, Sushma; Baniya, Ganga; Thapa, Madan; Sharma, Bhoj Raj; Sunar, Elisha (Journal of College of Medical Sciences-Nepal, 2024)
Background Paranasal sinuses are air-filled spaces present within some bones around the nasal cavities. These sinuses are rudimentary, or even absent at birth. They enlarge rapidly during 6 to 7 years of age. The aim of this study was to assess the diameters of maxillary sinuses and correlate the diameters with the patient’s age and sex. Methods Retrospective study was performed in the Department of Radiology and Imaging, Gandaki Medical College, Pokhara, Nepal during the period of December 2023 to March 2024. Data of 100 patients were collected who underwent CT PNS in which 56 were males and 44 were females. AP diameters, height, width and volume of both right and left maxillary sinuses were measured. Results The mean values of anteroposterior diameter, width, height and volume of right maxillary sinuses in males were 33.35 ± 3.45 mm, 20.41 ± 4.52 mm, 35.59 ± 5.73 mm and 12.57 ± 3.28 cc respectively and in left maxillary sinuses were 34.39 ± 3.53 mm, 21.89 ± 4.17mm, 36.02 ± 5.67mm, 13.76 ± 3.54 cc. Similarly, the mean values of anteroposterior diameter, width, height and volume of right maxillary sinuses in females were 31.46 ± 3.27mm, 18.10 ± 2.25mm, 35.57 ± 4.52mm ,10.74 ± 3.08 cc respectively and in left maxillary sinuses were 31.68 ± 3.29mm, 19.02 ± 3.16 mm, 35.73 ± 5.12 mm and 11.42 ± 3.64 cc. Conclusions There was statistically significant correlation with patient's gender, AP diameter, width and volume in male and female in both right and left maxillary sinuses except the right AP diameter of the maxillary sinuses. There was no statistical significant difference in male and female in height of both maxillary sinuses.